RESUSITASI OTAK PADA PASIEN CEDERA KEPALA BERAT DI RUMAH SAKIT UMUM PUSAT SANGLAH DENPASAR TAHUN 2020 - Dwikinta, Made Anindya; Mahadewa, Tjokorda Gde Bagus; Maliawan, Sri; Niryana, I Wayan (E-Jurnal Medika Udayana, 2024)
ABSTRACT Head injury is a serious problem worldwide and causes morbidity and mortality at a young age. The increase in the number of severe head injuries continues to occur along with the number of accidents. This study aimed to examine the characteristics of brain resuscitation in patients with a severe head injury. Descriptive research with cross-sectional research method and the data obtained as many as 35. Data processing using SPSS and displayed in a distribution table according to the variables. This study found that patients with severe head injuries were most often at the age of >45 years, namely 18 people (51.4%), and male sex was more common than women as many as 24 people (68.6%). The most common GCS was found with GCS 3-5 as many as 21 people (60%). The brain resuscitation regimen in patients with a severe head injury was given crystalloid solution (0.9% NaCl, Ringer's lactate) in 35 people (100%), mannitol 20% in 22 people (62.9%), and phenytoin in 33 people (94.3%). The GOS value of all patients with severe head injury with a GOS value of 1 or died (100%). Most deaths from severe head injury patients were in the first <48 hours as many as 27 people (77.1%) Keywords : brain resuscitation, traumatic brain injury, severe head injury.